Non‐Equilibrium Bose–Einstein‐Like Condensation. Issue 2 (6th June 2018) - Rodrigues, Clóves G.; Vannucchi, Fabio S.; Luzzi, Roberto
Abstract: The original Bose–Einstein condensation (BEC) was theoretically established in the 1920s, for the case of an ideal gas of boson particles (a consequence of the symmetry of the wave function). In the 1990s, it was realized in systems of atomic alkali gases. At the beginning of the 21st century, investigators considered its emergence in solid‐state matter, and a BEC‐like phenomenon was observed in the case of bosonic quasiparticles (elementary excitations in solids). Both types of BEC can occur in a condensation in conditions of thermodynamic equilibrium. A third type of what has been dubbed a BEC in non‐equilibrium conditions can occur in systems of bosonic quasiparticles (phonons, magnons, excitons); this phenomenon (which can be considered as cases of systems with complex behavior) follows after a certain threshold of intensity of an external pumping source is achieved. In this review, after brief comments on the two types of BEC in equilibrium, a description is presented on how a BEC‐like phenomenon arises in systems of quasiparticles that are driven away from thermodynamic equilibrium, and several examples are described. This description is given within a unique theoretical framework, and a comparison with experimental results is performed; in addition, the possible technological applications are outlined. Abstract : In this review, Rodrigues et al. describe how a Bose–Einstein condensation‐like phenomenon arises in systems of quasiparticles (phonons, magnons, excitons) that are driven away from thermodynamic equilibrium, and several examples are discussed. The description is presented within a unique theoretical framework, and a comparison with experimental results is performed; in addition, the possible technological applications are outlined.